Claimed effects, outcome variables and methods of measurement for health claims on foods related to the gastrointestinal tract proposed under regulation (EC) 1924/2006. (3rd October 2018) - Biasini, Beatrice; Marchi, Laura; Angelino, Donato; Bedogni, Giorgio; Zavaroni, Ivana; Pruneti, Carlo; Galli, Daniela; Mirandola, Prisco; Vitale, Marco; Dei Cas, Alessandra; Bonadonna, Riccardo C.; Passeri, Giovanni; et al.
Abstract: Most of the requests of authorisation to the use of health claims pursuant to Regulation EC 1924/2006 related to the gastrointestinal (GI) tract have received a negative opinion by the European Food Safety Authority (EFSA), mainly because of an insufficient substantiation of the claimed effect (CE). The present manuscript refers to the collection, collation and critical analysis of outcome variables (OVs) and methods of measurement (MMs) related to the GI tract compliant with Regulation 1924/2006. The critical evaluation of OVs and MMs was based on the literature review, with the final aim of defining their appropriateness in the context of a specific CE. The results obtained are relevant for the choice of the best OVs and MMs to be used in randomised controlled trials aimed to substantiate the claims on the GI tract. Moreover, the results can be used by EFSA for updating the guidance for the scientific requirements of such health claims. Graphical Abstract: